CaBi2Nb2O9 ceramic as well as preparation method and application thereof

Through microwave sintering technology and the addition of excessive Bi2O3, the problems of low piezoelectric response and resistivity of BLSF ceramics are solved, and high-efficiency piezoelectric performance and resistivity improvement at high temperatures are achieved, and are suitable for high-temperature vibration sensors.

CN119118649AActive Publication Date: 2024-12-13HUNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410590348.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2024-12-13
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

The piezoelectric response of existing high Curie temperature BLSF ceramics is poor. During the traditional sintering process, Bi2O3 volatilization leads to defects and low resistivity, making it difficult to effectively apply at high temperatures.

Method used

Using microwave sintering technology, by adding excess Bi2O3 to CaBi2Nb2O9 ceramics, ball milling is performed using zirconium dioxide balls and ethanol, combining axial compression and microwave sintering, the sintering time is shortened and the domain wall density and resistivity are improved.

Benefits of technology

It significantly improves the piezoelectric response and resistivity of CaBi2Nb2O9 ceramics, can work effectively above 700℃, and is suitable for high-temperature vibration sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118649A_ABST
    Figure CN119118649A_ABST
Patent Text Reader

Abstract

The invention provides a CaBi2Nb2O9 ceramic. The area of a ferroelectric domain in any cross section of the CaBi2Nb2O9 ceramic accounts for 14-18% of the area of the cross section; the length of a ferroelectric domain in the CaBi2Nb2O9 ceramic is 234 to 596 nm, and the thickness of the ferroelectric domain in the CaBi2Nb2O9 ceramic is 41 to 196 nm; the inverse piezoelectric coefficient of the zero electric field amplitude extrapolation of the CaBi2Nb2O9 ceramic is 6.5 to 6.8 pm / V; the Rayleigh coefficient of the CaBi2Nb2O9 ceramic is (0.15 to 0.18) * 10 <-17 > m < 2 > / V2; and the d33 of the CaBi2Nb2O9 ceramic at the normal temperature is 13 to 13.5 pC / N. The invention further discloses a preparation method of the CaBi2Nb2O9 ceramic. The invention also discloses a preparation method of the CaBi2Nb2O9 ceramic and an application of the CaBi2Nb2O9 ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic preparation, and in particular to a method for preparing a bismuth layered structure ferroelectric ceramic. Background Art

[0002] Since piezoelectric ceramics have the ability to convert electrical energy and mechanical energy into each other, they are widely used in various devices such as actuators, sensors, and energy harvesters. Harsh environment applications such as nuclear reactors and aviation turbines require a special class of piezoelectric ceramics that can operate at high temperatures above 600°C. However, high-performance perovskite structured piezoelectric ceramics, including lead zirconate titanate (PZT), barium titanate (BT), and potassium sodium niobate (KNN), have a Curie temperature below 500°C. On the other hand, high-Curie temperature piezoelectric ceramics, such as bismuth layered structure ferroelectric (BLSF) ceramics, have poor piezoelectric coefficients (d 33 ) and lower resistivity (ρ). Therefore, there is a strong driving force to improve the piezoelectric response of high Curie temperature BLSF ceramics.

[0003] Molecular formula for BLSF ceramics (Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- Indicates, where A represents Li + , Ca 2+ , Sr 2+ 、Bi 3+ ,La 3 + 、Ce 3+ Isohedral coordinated ions, B represents octahedral coordinated ions, such as Cr 3+ 、Co 3+ , Fe 3+ , Mn 4+ 、Ti 4+ 、Mo 5+ , W 6+ etc. CaBi2Nb2O9 (CBN, m=2) is a representative BLSF, which is calcium bismuth niobate, and it exhibits almost the highest Curie temperature (about 940℃) in the BLSF series. CBN ceramics are a promising candidate material that can be used as a key material for vibration sensors. The sensing element prepared by CBN can convert vibration into electrical signals at temperatures above 600℃. However, the spontaneous polarization of CBN ceramics is limited along the ab plane, resulting in d 33 The coercive field is relatively large. In addition, the volatilization of Bi2O3 during the traditional high-temperature sintering process often leads to a large number of defects, which reduces the resistivity of the ceramic. Extensive research is currently focused on developing composition engineering methods to adjust its microstructure and electrical properties. For example, by doping at the A site, B site or AB site, the d33 and ρ dc (600℃) were increased to 13~20pC / N and 10 5 ~10 6 The order of Ω·cm. However, conventional sintering requires a lot of time and high sintering temperature, and more importantly, it may lead to the formation of defects such as vacancy defects and pores. In addition, researchers have also developed texture densification sintering methods, including spark plasma sintering (SPS), hot pressing sintering (HP) and reactive template grain growth (TGG), to prepare textured piezoelectric ceramics, which exhibit enhanced piezoelectric response in a specific direction. However, the larger piezoelectric response along the texture direction is usually accompanied by unfavorable high conductivity.

[0004] Therefore, how to improve the piezoelectric response of high Curie temperature BLSF ceramics has become an urgent problem to be solved. Summary of the invention

[0005] The object of the present invention is to provide a high d 33 and ρ dc Preparation method of bismuth layered structure ferroelectric ceramics.

[0006] The present invention is achieved through the following technical solutions:

[0007] A CaBi2Nb2O9 ceramic, wherein the area of ​​the ferroelectric domain in any cross section of the CaBi2Nb2O9 ceramic accounts for 14-18% of the cross section area; the length of the ferroelectric domain in the CaBi2Nb2O9 ceramic is 234-596nm, and the thickness is 41-196nm; the inverse piezoelectric coefficient of the zero electric field amplitude extrapolated of the CaBi2Nb2O9 ceramic is 6.5-6.8pm / V; and the Rayleigh coefficient of the CaBi2Nb2O9 ceramic is 0.15-0.18×10 -17 m 2 / V 2 ; and the CaBi2Nb2O9 ceramic at room temperature 33 The preparation method of the CaBi2Nb2O9 ceramic comprises the following steps:

[0008] Adding 2-3 wt % of Bi2O3 to raw material powders of CaCO3, Bi2O3 and Nb2O5 in a molar ratio of 1:1:1 to obtain a raw material;

[0009] The raw material is ball-milled, dried and calcined, mixed with a binder, and ball-milled again to obtain a green body;

[0010] After the green body is debinded, it is microwave sintered at 935-945° C. to obtain the bismuth layered structure ferroelectric ceramic.

[0011] The grinding balls used in the ball mill include zirconium dioxide balls;

[0012] The medium used in the ball milling includes ethanol;

[0013] The time of gas ball milling is 20-30h.

[0014] The drying temperature is 40-6°C;

[0015] The drying time is 10-14 hours.

[0016] The forming comprises the step of axial pressing.

[0017] The axial pressing pressure is 150 MPa.

[0018] The debinding temperature is 600-700°C.

[0019] The calcination temperature is 800-900°C;

[0020] The calcination time is 2-3 hours.

[0021] The holding time of the microwave sintering is 9-11 minutes.

[0022] The microwave sintering uses microwaves with a frequency of 2.45 GHz and a power of 250 to 1250 W.

[0023] The binder includes ethyl cellulose, hydroxymethyl cellulose or methyl cellulose.

[0024] The CaBi2Nb2O9 ceramic is used for preparing vibration sensors.

[0025] The operating temperature of the vibration sensor is 0-700°C.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The CaBi2Nb2O9 ceramic provided by the present invention has thinner domain walls and higher domain wall density, so its piezoelectric performance is significantly enhanced.

[0028] The preparation method of the CaBi2Nb2O9 ceramic provided by the present invention uses microwave sintering (MS) to significantly improve the domain wall density of the CaBi2Nb2O9 ceramic and reduce the thickness of its domain wall.

[0029] The CaBi2Nb2O9 ceramic provided by the present invention can convert vibration into an electrical signal at a temperature of 700° C., so it can be used to prepare a vibration sensor working at a high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A shows the XRD patterns of CS1060, MS920, MS940, MS960 and MS980.

[0031] Figure 1 B shows Figure 1 A: Enlarged peak spectrum of the (008) peak.

[0032] Figure 1 C shows the Rietveld refined XRD pattern of CS1060.

[0033] Figure 1 D shows the Rietveld refined XRD pattern of MS940.

[0034] Figure 2 A shows the SEM image of the surface morphology of CS1060.

[0035] Figure 2 B shows the SEM image of the surface morphology of MS980.

[0036] Figure 2 C shows the SEM image of the surface morphology of MS960.

[0037] Figure 2 D shows the SEM image of the surface morphology of MS940.

[0038] Figure 2 E shows the SEM image of the surface morphology of MS920.

[0039] Figure 2 F shows the average grain size variation and length / thickness ratio of the surfaces of CS1060, MS980, MS960, MS940, and MS920 measured by NanoMeasurer.

[0040] Figure 3 A shows the SEM image of the internal morphology of CS1060.

[0041] Figure 3 B shows the SEM image of the internal morphology of MS980.

[0042] Figure 3 C shows the SEM image of the internal morphology of MS960.

[0043] Figure 3 D shows the SEM image of the internal morphology of MS940.

[0044] Figure 3 E shows the SEM image of the internal morphology of MS920.

[0045] Figure 3 F shows the average grain size variation and length / thickness ratio of CS1060, MS980, MS960, MS940, and MS920 measured by NanoMeasurer.

[0046] Figure 4 A shows the XPS spectra of the O1s core level obtained from CS1060 and MS 940 samples and the Gaussian-Lorentzian peak fitting plots.

[0047] Figure 4 B shows the spectra of Bi4f core levels obtained from CS1060 and MS940 samples and the Gaussian-Lorentzian peak fitting diagram.

[0048] Figure 5 A shows d 33 Variation of as a function of thermal depolarization temperature for CS1060, MS980, MS960, MS940, and MS920 ceramics.

[0049] Figure 5 B shows the relative d 33 Variation of as a function of thermal depolarization temperature for CS1060, MS980, MS960, MS940, and MS920 ceramics.

[0050] Figure 6 A shows the surface morphology of CS1060 after polishing.

[0051] Figure 6 B shows the surface morphology of MS940 after polishing.

[0052] Figure 6 C shows the amplitude graph of CS1060 after polishing.

[0053] Figure 6 D shows the amplitude graph of MS940 after polishing.

[0054] Figure 6 E shows the phase image of CS1060 after polishing.

[0055] Figure 6 F shows the phase image of MS940 after polishing.

[0056] Figure 7 A shows the unipolar strain-electric field diagram of CS1060.

[0057] Figure 7 B shows the monopolar strain-electric field diagram of MS940.

[0058] Figure 7 C shows that according to formula (1) 33 *=SP / E0 calculated d 33 *Data points in the graph, and linear fits to these data sets.

[0059] Figure 8 A shows the resistivity versus temperature graph for CS1060 and MS940 ceramics.

[0060] Figure 8 B shows the straight line graph of CS1060 and MS940 ceramics fitted by the Arrhenius function.

[0061] Fig. 9 A shows the impedance spectrum of CS1060 ceramic in the temperature range of 400 to 700°C.

[0062] Fig. 9 B shows the impedance spectrum of MS940 ceramic in the temperature range of 400 to 700°C.

[0063] Fig.10 A shows the relationship between the dielectric constant and temperature of CS1060 and MS940 ceramics at 1MHz. Fig.10 The inset in A is an enlarged view above 900°C.

[0064] Fig.10 B shows the relationship between the dielectric constant and temperature of CS1060 at 10kHz, 100kHz, and 1MHz. Fig.10 The inset in B shows the dielectric constant diagram at 500-600°C.

[0065] Fig.10 C shows the relationship between the dielectric constant and temperature of MS940 at 10kHz, 100kHz, and 1MHz. Fig.10 The inset in C shows the dielectric constant diagram at 500~600℃. DETAILED DESCRIPTION

[0066] The characterization method of the CaBi2Nb2O9 ceramic provided by the present invention is as follows:

[0067] The bulk density of ceramics is determined based on the Archimedean principle.

[0068] X-ray diffraction (XRD) patterns of the ceramics were collected using an X-ray diffractometer (MiniFlex600, Rigaku) ​​with Cu-Kα radiation (λ = 0.15406 nm) from 20° to 60° with a step size of 0.02° and a step size of 0.01° for the Rietveld refinement data.

[0069] The XPS spectra were obtained using an X-ray photoelectron spectroscopy (SHIMADZU, AXIS SUPRA+) with an Al target source (hν=1486.6 eV) and the C1s peak at 284.8 eV was used for calibration.

[0070] The microstructure of the sintered ceramics was characterized by scanning electron microscopy (ZEISS).

[0071] To study the electrical properties of the ceramics, the samples were polished on 600-grit sandpaper to a thickness of about 0.4 mm, and then coated with silver / platinum paste on both sides and heated at 600 °C for 10 min to obtain electrodes. 33 Through the quasi-static piezoelectric 33 Meter (ZJ-3AN) for measurement.

[0072] By measuring the room temperature d after annealing at different high temperatures ranging from 200 to 930 °C for 2 hours 33 The thermal stability of ceramic samples was evaluated by the changes in

[0073] The ferroelectric domains under the PFM model were observed using an atomic force microscope (Asylum Research MFP 3D).

[0074] The unipolar SE hysteresis curve was measured by a ferroelectric analyzer (TF-2000, aixACCT, Germany), and then the piezoelectric Rayleigh analysis was used to obtain d 33 * with the value of the applied electric field.

[0075] The temperature dependence of the resistivity was collected by a resistivity testing system (RMS1000+6517B) from 200°C to 700°C at a heating rate of 5°C / min.

[0076] The dielectric constant changes with temperature at different frequencies were measured by a dielectric temperature measurement system (DMS1000+WK6500). The AC impedance graph was measured using a high temperature impedance thermal imager (DMS1000+WK6500) in the temperature range of 400 to 700°C. The preparation method of the CaBi2Nb2O9 ceramic (abbreviated as CBN) involved in the present invention is as follows:

[0077] The amount of raw powder [CaCO3 (99.5%), Bi2O3 (99.99%), Nb2O5 (99.99%)] was determined according to the stoichiometric ratio of 1:1:1. In order to reduce the negative impact of Bi2O3 volatilization during calcination and subsequent sintering, an excess of 2.7wt.% of Bi2O3 relative to the raw powder was added. Then, the powder mixture was ground in a ball mill for 24 hours with the assistance of zirconium dioxide balls and ethanol (99.7%). The ground slurry was dried in an oven at 50°C for 12 hours and then calcined at 850°C for 2.5 hours. The obtained powder was crushed again under the same conditions. Subsequently, after adding a binder, axial pressing was carried out at a pressure of 150MPa to obtain a green body with a diameter of 10mm and a thickness of 0.8mm. The added binder can be ethyl cellulose. Finally, a silicon-molybdenum furnace (i.e., conventional sintering method, abbreviated as CS) was used to sinter at 1060°C for 2 hours (including heating and cooling for about 10 hours in total), and after burning off the binder at 650°C, a microwave sintering furnace (i.e., microwave sintering, abbreviated as MS) was used to sinter at 920°C, 940°C, 960°C, and 980°C for 10 minutes (including heating and cooling for about 2 hours in total). In the MS experiment, the sample was heated to the designed sintering temperature at a heating rate of 10°C / min. After sintering for 10 minutes, the furnace was started to cool to room temperature. The sample sintered at 1060°C was recorded as CS1060.

[0078] The sample sintered at 920°C was designated as MS920.

[0079] The sample sintered at 940 °C was designated as MS940.

[0080] The sample sintered at 960°C was designated as MS960.

[0081] The sample sintered at 980 °C was designated as MS980.

[0082] Specifically, the furnace of the microwave sintering furnace is provided with a silicon carbide plate. The microwave sintering furnace operates at a frequency of 2.45 GHz and heats the sample and the external silicon carbide plate at a high power of 250 to 1250 W. The silicon carbide plate can also absorb microwave energy and quickly heat up as an auxiliary heater in the early stage of sintering.

[0083] For the CS method, heat is transferred from the surrounding heat source to the green body by convection, conduction or radiation. In other words, during the CS process of CBN ceramics, heat is transferred from the surface to the inside. As a result, an inhomogeneous temperature field is generally generated inside the green body, resulting in inconsistent grain crystallization dynamics and inconsistent shrinkage of the ceramic body. High sintering temperatures (e.g., 1060°C) and long sintering times (~10 hours) are not good for CBN ceramics because the volatilization of bismuth oxide will produce oxygen vacancies in the sample. Therefore, the piezoelectric coefficient (d33 ) is poor, resistivity (ρ dc ) is lower.

[0084] However, the sintering mechanism of the MS method is different from that of the CS method. A microwave source is used to generate high-energy microwaves of a certain frequency (2.45GHz), which resonate with the internal molecules of the sample and provide a large amount of energy for uniform heating. In addition, the surrounding external silicon carbide plates serve as a supplementary heat source, which helps to obtain a uniform temperature field. Compared with CS, the atomic diffusion barrier of MS is lower, resulting in accelerated atomic diffusion and rapid sintering. Therefore, MS is conducive to shortening the sintering time (2 hours) and obtaining a dense, fine and uniform grain morphology. Figure 1 A shows the comparison of XRD patterns obtained from CS1060, MS 980, MS 960, MS 940, and MS 920 samples. The diffraction peaks of all ceramic samples can be indexed to orthorhombic phases using the PDF#49-0608 standard card. The highest diffraction peak is denoted as the (115) diffraction plane, which corresponds to the strongest diffraction plane (112m+1) in BLSF ceramics, since the m value of CBN is equal to 2. Figure 1 As shown in Figure B, in addition to the (008) diffraction peak, another small peak can be observed at a higher angle on the shoulder of the (008) peak for all MS samples. It is worth noting that other small peaks from impurities can be observed in other areas. Interestingly, the XRD pattern of CBN ceramics sintered at 940°C using the CS method also shows these small peaks. Therefore, due to the low microwave sintering temperature and excess Bi2O3, this method may cause a small amount of unexpected bismuth-containing second phase to appear in CBN.

[0085] To further investigate the effect of MS on CBN ceramics, all samples were subjected to Rietveld refinement in the range of 10–90° according to the crystal model reported by Black et al. Figure 1 As shown in B and C, the calculated results are consistent with the collected XRD data. P (5.99-7.24%), R wp The refinement factors of Chi2 (9.27-10.3%) and Chi2 (4.24-5.11) are also in a reasonable range. Table 1 lists the calculated lattice parameters a, b, c and orthogonal parameters 2(ab) / (a+b). The orthogonal parameters of microwave sintered ceramics are lower than those of conventionally sintered samples. In addition, the parameters of MS 920 are significantly reduced compared with other microwave sintered samples, which may be due to the sintering temperature being lower than the Curie temperature and the cooling rate being significantly faster than conventional sintering. In addition, the parameters of MS920 are significantly reduced compared with other microwave sintered samples. These results indicate that MS is beneficial to improving the tetragonality of CBN.

[0086] Table 1. Structural parameters of CS1060, MS 920, MS 940, MS 960 and MS 980 ceramics.

[0087]

[0088] Figure 2 (A)-(E) show the surface morphology of CBN ceramics shown in SEM images. From the figure, it can be seen that CBN ceramics are closely packed with plate-like or rod-like grains, and there are no obvious pores or intergranular impurities in CBN ceramics. In traditional sintered ceramics, small rod-like grains are located at the junction of several large plate-like grains ( Figure 2 A), which results in a wide grain size distribution and a large length / thickness ratio ( Figure 2 F). This phenomenon is mainly due to the inherent layered structure of BLSF and the uneven temperature field in the ceramic plate during conventional sintering, which leads to preferential growth along the ab plane. In contrast, the grains of microwave sintered ceramics show a uniform rod-like structure. Similar morphology, the grain size is about 1 μm ( Figure 2 (BE)), which is much smaller than that of conventional sintered ceramics (3.5 μm). As the sintering temperature decreases, the average grain size and length / thickness ratio gradually decrease ( Figure 2 F). Direct volumetric heating in the green body will provide a relatively uniform temperature field, which is conducive to grain growth within the duration of temporary microwave sintering (10 minutes). In addition, low sintering temperatures and residence times will produce small grain sizes as well as obvious porosity, as shown in the MS 920 sample. Since the sintering mechanism of the MS method is different from that of the CS method, the present invention conducted additional SEM characterization by polishing representative bulk samples, reducing their thickness from ~0.8mm (surface) to ~0.5mm (interior). After high-temperature etching at 920°C, the internal microstructure of these samples was revealed using scanning electron microscopy technology. As shown Figure 3 As shown in Figure 2, the microstructure inside the sample is Figure 2 The surface microstructure shown is consistent. Compared with the CS sample, the average grain size of the MS sample is significantly reduced. In addition, the MS 940 sample has the smallest grain size and significantly reduced anisotropy. Table 2 shows the density of CS1060 and MS 940 ceramics. The relative density and theoretical density of MS 940 ceramics are greater than those of CS1060 ceramics, which further verifies that microwave sintering can reduce sintering defects and vacancies and improve the degree of densification.

[0089] Table 2. Comparison of experimental density, theoretical density and relative density of CS1060 and MS 940 ceramics

[0090]

[0091] In order to detect the types of volatiles during sintering, the green body was placed in a high-temperature furnace at 650°C to burn off the binder, and then its initial mass was measured, followed by CS and MS, and finally weighed again after sintering to obtain the mass loss during sintering. As shown in Table 3, the mass volatilization ratios of CS1060 and MS 940 samples before and after sintering were 0.57% and 0.13%, respectively. We note that the melting points of the raw materials Bi2O3, Nb2O5 and CaO are 825°C, 1520°C and 2572°C, respectively. Since Bi2O3 has the lowest melting point, which is much lower than the sintering temperature of CS and MS (940-1060°C), it can be preliminarily inferred that the reduced part is mainly Bi2O3 compounds. This result shows that the MS method can inhibit the volatilization of Bi2O3. In order to further confirm the volatilization of Bi2O3, the present invention uses XPS to characterize the samples, and uses Gauss-Lorentz peak fitting to compare the spectral changes of O1s and Bi 4f in MS 940 and CS1060 samples. Figure 4 As shown in Figure A, at 531.6 eV, the area ratio of the b peak [b / (a+b)] decreases from 62.5% in the CS1060 sample to 52.6% in the MS 940 sample. This observation indicates that the oxygen vacancy concentration in the MS 940 sample is significantly reduced compared to the CS1060 sample. In addition, as Figure 4 As shown in Figures AB, the binding energies of the O1s and Bi 4f peaks in the spectrum of the MS 940 sample are significantly shifted to a higher direction compared to the CS1060 sample, further indicating that the chemical bond between bismuth and oxygen atoms in the MS 940 sample is tighter than that in the CS1060 sample. This is another evidence that the oxygen vacancy concentration in the MS 940 sample is lower.

[0092] Table 3. Mass volatilization ratio of CS1060 and MS 940 samples before and after sintering.

[0093]

[0094] In order to examine the difference in piezoelectric response between microwave-sintered and conventionally sintered ceramics, d 33 and thermal depolarization were characterized. Figure 5 A and Figure 5 As shown in B, CS1060 ceramic 33 is 7.2pC / N. In MS series ceramics, when the sintering temperature is 940℃, d 33 The highest is 13.4pC / N. By using microwave sintering, d 33 The significant enhancement is attributed to the smaller grain size and the increased densification of MS ceramics. First, the domain size depends on the grain size, and the relationship is domain size ∝ (grain size) m. The increase in domain wall density in small-sized ceramics is conducive to the improvement of piezoelectric response. Secondly, smaller grains and higher densification generally allow CBN ceramics to withstand higher breakdown electric fields. Therefore, these fine-grained samples are more likely to be fully polarized. In the present invention, the CBN samples prepared by MS have smaller grains and denser morphology, and can withstand higher polarization electric fields (18 kV / mm) compared with the CBN samples prepared by CS (14 kV / mm).

[0095] Since thermal stability is critical for high temperature applications, the present invention measures d 33 The difference between microwave sintered ceramics and conventional sintered ceramics in improving thermal stability was evaluated by changing the annealing temperature. Figure 5 As shown in Figure 2, when the annealing temperature is increased to 400°C, the d 33 Only about 10% decreases, which can be attributed to the unstable non-180° domains. As the temperature rises above 800°C, severe thermal depolarization is established in both conventionally sintered ceramics and microwave sintered ceramics, and as the depolarization temperature further increases to 930°C close to the Curie temperature and microwave sintering, d 33 As for MS 920, d 33 The continuous decrease with increasing annealing temperature is most likely caused by incomplete sintering. These results strongly suggest that microwave sintering is a feasible method to improve the piezoelectric coefficient and thermal stability of CBN ceramics.

[0096] In order to gain a deeper understanding of the improvement of piezoelectric response, the present invention used piezoresponse force microscopy (PFM) to observe the ferroelectric domains of MS940 and CS1060 samples. Figure 6 As shown. The amplitude image shows that the amplitude intensity of the MS 940 sample is nearly two times greater than that of the CS1060 sample, indicating that the piezoelectric response of the MS 940 sample is greater. This observation is in good agreement with the results of the strain-electric field experiment (see Rayleigh analysis below). In addition, the MS 940 sample shows thinner and more evenly distributed strip-like domains. PFM studies clearly show that the domain wall density of the MS 940 sample has increased compared to the CS1060 sample, and thinner domain walls and higher domain wall density are conducive to the enhancement of piezoelectric properties.

[0097] In order to prove the contribution of domain wall motion to piezoelectricity, the present invention uses a ferroelectric analyzer (TF-2000, aixACCT, Germany) to test the unipolar SE hysteresis curve of the sample and uses piezoelectric Rayleigh analysis to obtain d 33 * The value changes with the applied electric field. The inverse piezoelectric strain coefficient under different electric fields is obtained by the following formula. Figure 7As shown in AB, within the measured electric field range, both MS 940 and CS1060 samples present unsaturated unipolar SE curves, which indicates that MS 940 and CS1060 can trigger domain wall motion under the action of an external electric field. The present invention also uses formula (1) to calculate the inverse piezoelectric strain coefficient under various electric field amplitudes.

[0098] Formula (1) is d 33 * =S P / E0. In the formula, S P is the peak strain at each maximum electric field amplitude, E0 is the corresponding maximum electric field amplitude, d 33 * is the inverse piezoelectric coefficient.

[0099] Formula (2) can be used to study the Rayleigh behavior of the piezoelectric strain coefficient and the electric field amplitude.

[0100] Formula (2) is d 33 * =d init +αE where d init is the inverse piezoelectric coefficient extrapolated from zero electric field amplitude, α is the Rayleigh coefficient, E is the electric field amplitude, and αE is the contribution of irreversible domain wall motion.

[0101] like Figure 7 As shown in C, the MS 940 sample has a larger d init (~6.76pm / V) and α (~0.17×10 -17 m 2 / V 2 ) value. Where αE is the contribution of irreversible domain wall motion, including intrinsic lattice strain and intrinsic reversible domain wall motion. Therefore, the d init The increase of α and α indicates that the domain wall motion is easier. In addition, domain wall motion, including reversible and irreversible domain wall motion, will lead to nonlinear piezoelectric response and strain hysteresis. Large strain hysteresis and residual strain also confirm the enhanced domain wall motion of MS 940 specimen. PFM measurement results show that the enhancement of domain wall motion is mainly due to the reduction of domain size. 33 * greater than d 33 This may be due to the large coercive field in CBN ceramics, which makes it difficult to fully polarize during the polarization process. 33 In addition, the resistivity at high temperature (ρ dc ) is also critical for high temperature vibration sensor applications. The MS 940 and CS1060 dc The relationship with temperature is Figure 8 A. The MS 940 sample exhibits a larger ρ dc ρ of MS 940 and CS1060 at 600℃dc 7×10 5 and 4×10 5 Ω·cm, which is higher than the existing CBN value (~6×10 4 Ω·cm) is nearly one order of magnitude larger. dc The enhancement of is attributed to the improved densification, as indicated by the increased density using MS compared to the CS method. In principle, the conduction mechanism in the different temperature regions can be explained by the Arrhenius equation as follows:

[0102]

[0103] where ρ0 refers to the prefactor, E a is the conduction activation energy, k B is the Boltzmann constant and T is the absolute temperature. Figure 8 B shows the ρ of MS 940 and CS1060 dc Changes with temperature. These curves can be divided into low temperature zone (≤300℃) and high temperature zone (≥300℃). In the low temperature zone, the E a They are 1.114eV and 1.096eV respectively. a The value is in the range of 0.6 to 1.4 eV, indicating that the conductivity is mainly based on oxygen vacancies and holes. In the high temperature region, the Ea of MS 940 and CS1060 increases to 1.463 eV and 1.366 eV, respectively. a The values ​​are in the range of 1.4 to 1.8 eV, indicating that the conduction mechanism of MS is intrinsic thermally activated conduction, while CS is still dominated by oxygen vacancies and holes. a It is likely that the MS method can alleviate the volatilization problem of bismuth oxides, thereby suppressing the generation of oxygen vacancies, which is also revealed by XPS analysis and mass loss measurement.

[0104] Fig. 9 AB are the impedance spectra of CS1060 and MS 940 ceramics at 400-700℃. The impedance decreases with the increase of temperature, which is consistent with Figure 8 The temperature dependence of ρdc in the CS1060 ceramic is consistent. It is observed that the impedance spectrum of the CS1060 ceramic exhibits three semicircular graphs, while the MS 940 ceramic exhibits almost only one semicircular graph. Fig. 9 As shown in A, the grain effect (R G ), grain boundary effect (R GB ) and ion diffusion effect (W) form three semicircular graphs. However, the grain boundary effect (R GB ) and ion diffusion effects (W) appear to be suppressed ( Fig. 9 B).

[0105] In order to study the effect of microwave sintering on the dielectric properties of CBN ceramics, the temperature dependence of the dielectric constant of CS1060 and MS 940 ceramics at 1 MHz was collected. Fig.10 As shown in Figure A, the dielectric constants of CS1060 and MS 940 ceramics increase with increasing temperature and decrease rapidly after reaching the Curie point, which is related to the transition of CBN ceramics from ferroelectric phase to quasi-electric phase. The Curie point also increases slightly from 931℃ for CS to 935℃ for MS. Fig.10 As shown in BC, the CS1060 sample exhibits a dielectric peak between 500°C and 600°C, which weakens with increasing frequency. In the MS 940 sample, the dielectric peak disappears, which corresponds to the suppression of oxygen vacancies in the ceramic.

[0106] In summary, the present invention first provides a CaBi2Nb2O9 ceramic, wherein the area of ​​the ferroelectric domain in any cross section of the CaBi2Nb2O9 ceramic accounts for 14-18% of the cross section area; and the length of the ferroelectric domain in the CaBi2Nb2O9 ceramic is 234-596nm, and the thickness is 41-196nm; because the above domain structure is thinner and more slender, and at the same time, the number is also greater, so the domain wall movement is easier. The increase in domain wall movement can increase the piezoelectric coefficient of the CaBi2Nb2O9 ceramic. Therefore, the d of the CaBi2Nb2O9 ceramic at room temperature is 33 The inverse piezoelectric coefficient of the CaBi2Nb2O9 ceramic is 6.5-6.8 pm / V, and the Rayleigh coefficient of the CaBi2Nb2O9 ceramic is 0.15-0.18×10 -17 m 2 / V 2 The inverse piezoelectric coefficient d is extrapolated from the zero electric field amplitude. init and the increase in the value of the Rayleigh coefficient α indicates that the domain wall motion is easier.

[0107] The CaBi2Nb2O9 ceramic provided by the present invention is prepared by a microwave sintering method. The microwave sintering can shorten the sintering holding time to reduce the volatilization of bismuth oxide, which makes the domain structure of the CaBi2Nb2O9 ceramic thinner and more slender, and is easier to produce domain wall movement. The domains in the CaBi2Nb2O9 ceramic are tiny areas in the ferroelectric with the same spontaneous polarization direction. Obviously, the oxygen vacancies caused by the volatilization of bismuth oxide will prevent the formation of this structure. At the same time, the control of the sintering temperature is also important. When the CaBi2Nb2O9 ceramic is sintered at around 940°C, the sample can complete the sintering quickly, saving a lot of time and energy, while obtaining a higher d 33 And piezoelectric ceramics with more uniform, finer grains and higher density.

[0108] Specifically, the microwave sintering comprises the following steps:

[0109] The raw material is obtained by adding 2-3wt% Bi2O3 into raw material powders of CaCO3, Bi2O3 and Nb2O5 in a molar ratio of 1:1:1; the raw material is ball-milled, dried and calcined, and ball-milled again with a binder to obtain a green body; the green body is debinded and microwave sintered at 935-945°C to obtain the bismuth layered structure ferroelectric ceramic.

[0110] The CaBi2Nb2O9 ceramic can be used to prepare a vibration sensor. Since the piezoelectric coefficient of the CaBi2Nb2O9 ceramic begins to decrease at 800°C, the working temperature of the vibration sensor prepared from the CaBi2Nb2O9 ceramic is 0-700°C.

[0111] At the same time, the relative density of microwave sintered CBN ceramics is 99.6%, which is higher than the 98.5% of conventional sintered ceramics. After microwave sintering, the average grain size is reduced from 3.5μm to 1μm, and the grain size distribution is more uniform. 33 (13.4pC / N) is much higher than the d of conventional sintered CBN ceramics 33 (7.2pC / N). 33 The significant enhancement of ρ is due to the increased domain wall density and more complete polarization of the CBN ceramic with improved grain size and densification. dc (7×10 5 Ω·cm) is higher than CS1060 dc (4×10 5 Ω·cm), which is due to the suppression of the volatilization of Bi2O3 and the reduction of the number of vacancy defects. In summary, compared with the CBN ceramics prepared by CS, the CBN ceramics prepared by MS have higher piezoelectric response and resistivity at high temperature and can be used to prepare high-temperature vibration sensors.

Claims

1. A CaBi2Nb2O9 ceramic, characterized in that: The area of ​​the ferroelectric domain in any cross section of the CaBi2Nb2O9 ceramic accounts for 14-18% of the cross section area; and The length of the ferroelectric domain in the CaBi2Nb2O9 ceramic is 234-596nm and the thickness is 41-196nm; and The inverse piezoelectric coefficient of the CaBi2Nb2O9 ceramic is 6.5-6.8 pm / V extrapolated from the zero electric field amplitude; and The Rayleigh coefficient of the CaBi2Nb2O9 ceramic is 0.15-0.18×10 -17 m 2 / V 2 ;and The CaBi2Nb2O9 ceramics at room temperature 33 It is 13-13.5pC / N.

2. The method for preparing the CaBi2Nb2O9 ceramic according to claim 1, characterized in that: The steps include: Adding 2-3 wt % of Bi2O3 to raw material powders of CaCO3, Bi2O3 and Nb2O5 in a molar ratio of 1:1:1 to obtain a raw material; The raw material is ball-milled, dried and calcined, mixed with a binder, and ball-milled again to obtain a green body; After the green body is debinded, it is microwave sintered at 935-945° C. to obtain the bismuth layered structure ferroelectric ceramic.

3. The method for preparing the CaBi2Nb2O9 ceramic according to claim 2, characterized in that: The grinding balls used in the ball mill include zirconium dioxide balls; The medium used in the ball milling includes ethanol; The time of gas ball milling is 20-30h; The binder includes ethyl cellulose, hydroxymethyl cellulose or methyl cellulose.

4. The method for preparing the CaBi2Nb2O9 ceramic according to claim 2, characterized in that: The drying temperature is 40-60°C; The drying time is 10-14 hours.

5. The method for preparing the CaBi2Nb2O9 ceramic according to claim 2, characterized in that: The forming comprises the step of axial pressing.

6. The method for preparing the CaBi2Nb2O9 ceramic according to claim 5, characterized in that: The axial pressing pressure is 150 MPa.

7. The method for preparing the CaBi2Nb2O9 ceramic according to claim 2, characterized in that: The debinding temperature is 600-700°C.

8. The method for preparing the CaBi2Nb2O9 ceramic according to claim 2, characterized in that: The calcination temperature is 800-900°C; The calcination holding time is 2-3 hours; The holding time of the microwave sintering is 9-11 minutes; The microwave sintering uses microwaves with a frequency of 2.45 GHz and a power of 250 to 1250 W.

9. The use of the CaBi2Nb2O9 ceramic according to claim 1, characterized in that: Used in the preparation of vibration sensors.

10. The use of the CaBi2Nb2O9 ceramic according to claim 9, characterized in that: The operating temperature of the vibration sensor is 0-700°C.

Citation Information

Patent Citations

  • Piezoelectric material, piezoelectric element, liquid discharge head, ultrasonic motor, and dust cleaning device

    CN102934247A

  • Calcium bismuth niobate high-temperature piezoceramic material of bismuth layer structure and preparing method of calcium bismuth niobate high-temperature piezoceramic material

    CN106554203A

  • Sodium bismuth titanate-based lead-free piezoelectric ceramic by using microwave material science workstation, and preparation method thereof

    CN109721352A

  • Piezoelectric ceramic material

    EP1178025A2